Penerapan Permainan Ular Tangga dalam Peningkatan Hasil Belajar Geometri Bangun Ruang di Kelas v SD 006 Rambah Samo - munadah, reny; Rahayu, Puput Sri; Pranandari, Erliska; Jukia, Fitri; Rosdianti, Vera (Trapsila: Jurnal Pendidikan Dasar, 2021)
Abstract Â This study aims to determine the increase in student learning outcomes through learning media for the game of snakes and ladders. The subjects of this study were 15 students of grade V SD 006 Rambah Samo, which amounted to 15 people in the 2020/2021 school year. This study consisted of 2 cycles consisting of the stages of planning, action, observation, and reflection. The instruments used to measure the improvement of student learning outcomes are test instruments and non-test instruments in the form of observation sheets, field notes, and documentation. The data obtained from the research results were analyzed using quantitative descriptive research, namely data in the form of numbers and can be expressed in units of count. The results of the data analysis showed that there was an increase in student learning outcomes in class V SD 006 Rambah Samo, after applying the playing method using snake and ladder medis by 26,67%. This can be seen from the increase in the average percentage of student learning outcomes in cycle 1 of 6,66% and in cycle 2 amounted to 33,33%. The small percentage of student learning outcomes who reach the KKM is due to constraints in online learning that were less effective during the Covid-19 pandemic.